PENGARUH PENGORBANAN DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG - Gendut Sukarno; Sumarto Sumarto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
This study investigates The Conceptual Model of Decision Making of Repeat Buying motorbike Honda in 20 (twenty) dealer Sale of Honda in Surabaya. This research expected can assist heads of dealer in taking decision related to Sacrifice and Quality Service with Value Service and Consumer Satisfaction, and its influence to Decision of Repeat Buying motorbike honda. According to sacrifice released by consumer to get service and product become big especial size measure the so small service value. Company (dealer) in submitting service and provide the quality of service represent all important matter in creating value to customer and his innings will be able to determine service value. Synergity among service value and satisfaction of consumer give contribution to decision of consumer in repeat buying motorbike Honda in Surabaya.Sampel in this research are repeat buyers and user of motorbike honda in region of Surabaya as responder counted 106 people. Analysis technique in this research used Structural Equation Modelling [SEM] one step & two step approach with program AMOS 4,0. Result of examination find that inexistence of multikolinierity in sacrifice, quality of service, service value, and satisfaction of consumer and also decision of repeat buying.Service value not yet earned to give influence of signifikan to sacrifice. Service value can give influence of signifikan to quality of service. While satisfaction of consumer not yet earned to give influence of signifikan to service value, but signifikan to quality of service. Decision of repeat buying can give influence of signifikan to quality of service, but not signifikan to consumer satisfaction